Thermal and hygroscopic study of hemp concrete in real ambient conditions - Asli, M.; Brachelet, F.; Sassine, E.; Antczak, E. (Journal of Building Engineering, 2021)
Most building materials, and more particularly bio-based materials, are subject to hygrothermal transfers in the environment in which they are disposed. These transfers depend on their thermophysical characteristics as well as the ambient humidity and temperature conditions. In such environment, and despite these variations, the material must be able to ensure in a sustainable manner, the functions for which it was implemented (thermal, mechanical, acoustic …). Among these materials, hemp concrete, which is a bio-based material, is widely considered in building construction for its superior thermal and hygroscopic performance. The hygrothermal modelling of such materials in real conditions is essential for a better understanding of buildings’ energy performances. Several works targeted the numerical hygrothermal modelling of hemp concrete; however most of them are done in controlled laboratory conditions, which may be different from the real buildings scenarios. In this paper, heat and mass transfer are investigated both numerically and experimentally in real conditions. The hygrothermal properties of hemp concrete were first determined through laboratory experiments; then, an experimental wall segment made of hemp concrete was instrumented in real ambient conditions in order to validate the Philip and De Vries model describing heat and mass transfer. The comparison of the numerical results to the experimental data leads to interesting results regarding local temperature and relative humidity variations. Moreover, numerical investigation of the moisture buffer values of hemp concrete was performed and the results were validated by bibliographic data. The hemp concrete was found to be a very interesting potential hygrothermal regulation material in terms of thermal conductivity, decrement factor, time lag, and humidity regulation. •The material's thermophysical properties of hemp concrete were experimentally determined using an thermal characterization experimental setup.•A hemp concrete wall was instrumented with temperature and humidity sensors and exposed to real weather conditions.•A numerical model describing heat and mass transfer was adopted and compared to experimental measurements.•To study the efficiency of hemp concrete in regulating the ambient humidity, a numerical investigation of the Moisture Buffer Value was performed.•According the Nordtest classification, the hemp concrete can be classified between good and excellent humidity regulator materials.